Measles – are we dealing with a new epidemy in Poland? - Maciej Rutkowski; Łukasz Świerszcz; Anna Roszkowska; Anna Taracha; Halina Piecewicz-Szczęsna (Journal of Education, Health and Sport, 2017)
Introduction: In the past few years, a group of parents avoid mandatory vaccination of children has increased. One of the effects of this action is increasing incidence of measles among unvaccinated people. The knowledge of current trends enables us to design and develop education programs for parents and to deny the distortion inherent myths about vaccinations.